2005
DOI: 10.1128/jb.187.24.8256-8266.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Detachable Rho-Dependent Transcription Terminator of the fimE Gene in Escherichia coli K-12

Abstract: The fim genetic switch in the chromosome of Escherichia coli K-12 is an invertible DNA element that harbors the promoter for transcription of the downstream fim structural genes and a transcription terminator that acts on the upstream fimE regulatory gene. Switches oriented appropriately for structural gene transcription also allow fimE mRNA to read through, whereas those in the opposite orientation terminate the fimE message. We show here that termination is Rho dependent and is suppressed in a rho mutant or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 63 publications
(93 reference statements)
0
25
1
Order By: Relevance
“…Whether the decreased expression of fimB and fimE is sufficient to explain the observed phenotype of BEN2908 ⌬ibeA will have to be investigated. It has been shown that when the IE is in the off orientation, the RNA encoding fimE is unstable due to early rho-dependent termination (22,27). It is therefore possible that the reduced level of fimE RNA that we observed was only a consequence, and not the cause, of the larger proportion of IE in the off orientation.…”
Section: Discussioncontrasting
confidence: 39%
“…Whether the decreased expression of fimB and fimE is sufficient to explain the observed phenotype of BEN2908 ⌬ibeA will have to be investigated. It has been shown that when the IE is in the off orientation, the RNA encoding fimE is unstable due to early rho-dependent termination (22,27). It is therefore possible that the reduced level of fimE RNA that we observed was only a consequence, and not the cause, of the larger proportion of IE in the off orientation.…”
Section: Discussioncontrasting
confidence: 39%
“…Feedback between the switch state and the switch flipping rate arises because the FimE recombinase (which flips the switch in the on to off direction), is produced more strongly in the on switch state than in the off state. This phenomenon is known as orientational control [29,30,31]. The production of a second type of fimbriae in uropathogenic E. coli, Pap pili, also phase varies, and is controlled by a DNA methylation switch [1,2,32].…”
Section: Introductionmentioning
confidence: 99%
“…In serovar Typhimurium, the fimU gene specifies a rare arginine tRNA that modulates the translation of the mRNA expressed by the fimY regulatory gene (73). In E. coli, a detachable Rho-dependent transcription terminator modulates the rate of turnover of an mRNA expressed by one key regulatory gene (40,45) while a rare leucine tRNA encoded by the leuX gene influences the rate of translation of another (65). Mutations in the serovar Typhimurium fimU locus inhibit fimY translation and lead to an afimbriate phenotype (73).…”
mentioning
confidence: 99%